Looking for social class and civil society in political discourse in Portuguese democracy (1976-2006) - content analysis approach - Santo, Paula do Espírito (2015)
Political discourse gives an important clue to the importance of key concepts with ideological political relevance, in the political system. That is the case of social class, religion and political parties, considering their role in political and electoral terms. The social class concept has been long and widely debated in political sociology. Its importance in political language and discourse is the key issue of this research. The focus of this study is the importance of social class, considering the segmentation of different civil society groups as expressed in political discourse. The aim is to analyse political speeches made by the most important political actor in the nation, the President. Our scope of analysis covers the timeline since the first stages in Portuguese democracy following the Revolution of April 1974, and extends until 2006. Content analysis technique will be used to address it. The expected results point towards the loss of importance of social class, as a traditional key concept, which evolved in quite extensive ways, in its application to contemporary political messages. This study tends to converge with the mainstream literature that has elaborated on the structural and permanent loss of importance of social class in politics, including in electoral terms.